Exploring the Impact of Assessment on Medical Students' Learning. Issue 1 (2nd January 2020) - Preston, Robyn; Gratani, Monica; Owens, Kimberley; Roche, Poornima; Zimanyi, Monika; Malau-Aduli, Bunmi
Abstract: What and how students learn depend largely on how they think they will be assessed. This study aimed to explore medical students' perception of the value of assessment and feedback on their learning, and how this relates to their examination performance. A mixed methods research design was adopted in which a questionnaire was developed and administered to the students to gain their perceptions of assessments. Perceptions were further explored in focus group discussions. Survey findings were correlated with students' performance data and academic coordinators' perceptions. Students' perceptions of the level of difficulty of different assessments mirrored their performance in examinations, with an improvement observed in clinical assessments as students progressed through their degree. Students recognised that feedback is important to allow improvements and seek more timely, better quality and personalised feedback. Academic coordinators identified that some of the students' suggestions are more realistic than others. Students had a positive attitude towards assessment, but emphasised the need for educators to highlight the relevance of assessment to clinical practice.